PO205 A prospective clinical and immunological study of late onset myasthenia gravis. (1st December 2017) - Sadalage, Girija; Jacob, Saiju; Hilton-Jones, David; Buckley, Camilla; Vincent, Angela; Maddison, Paul
Abstract : Introduction: Epidemiological studies conducted in several countries have shown that the incidence of myasthenia gravis in the older population (>50 years) is increasing. We were interested in establishing if there were different clinical and immunological features between early (EOMG) and late onset myasthenia gravis (LOMG). Methods and Results: We have recruited 150 patients making this the largest prospective cohort study in MG to date with 100% recruitment rates in the Trent region. Most (72.7%) patients had LOMG. Comparison between MG composite scores shows that disease severity at diagnosis was greater (p=0.0339) and antibody titres higher (p=0.007) in the LOMG group compared to EOMG. This was not entirely because of pure ocular presentation, which was observed at similar rates between both patient groups (48% EOMG, 36% LOMG, p=0.24) There was a significant fall in Acetylcholine receptor Antibody titres with time, in keeping with improved MG composite scores (p<0.0001) both in patients who were and were not given immunosuppression. Conclusion: Our prospective cohort study shows that the incidence of LOMG is indeed much higher than EOMG with greater disease severity in LOMG pts at diagnosis. Immunological studies are ongoing and should add to the clinical data already collected.